Opportunities for city carbon footprint reductions through imports source shifting : the case of Bogota (2021)
Achieving the Paris Agreement goals calls for higher ambition across actors. In this article, we address the carbon emission responsibility of the city of Bogota from a consumption-based perspective, by assessing the carbon footprint for the whole city. We use an environmentally extended multiregional input-output model where a survey-based input-output table of Bogota is nested, avoiding the downside of using assumptions regarding the production and trade structure of the city. We identify city's emissions hotspots across the globe, mainly in China and the United States, proving that consumption-based accounting is required when highly open systems as cities are under analysis, to finally propose source shifting scenarios as mitigation strategies. Our results indicate that Bogota is a net importer of CO2 emissions and, the city's carbon footprint almost double direct emissions generated within its territory. China, the rest of Colombia, and the United States are heavily affected by Bogota's carbon footprint as those three regions bear 38% of the city's footprint. The main drivers of those emissions are Electrical equipment, Computers, Vehicles and Machinery, goods that are imported and consumed by Bogota's residents. Important opportunities for emission reductions arise when sourcing changes from China to the US and Latin American countries, which provide fresh evidence for national and local authorities to improve their efforts on reducing emissions.